Evaluasi Program Tahfidz dengan Model CIPP [Context, Input, Process, Product] di Sekolah Dasar Integral Al-Bayan Makassar - ِAbdul Kadir; Siti Syamsudduha; Muhammad Nur Akbar Rasyid (ISLAMIKA, 2023)
This research aims to evaluate the context, input, process and output components of the Tahfidz Qur'an program at SD Integral Al-Bayan Makassar. This is a descriptive qualitative method using CIPP model. This research involved the Principal, the coordinators of Tahfidz Qur'an, teachers and the fifth grade students of Al-Bayan Integral Elementary School Makassar. Based on the results of evaluation, it can be concluded that the Tahfidz Qur'an program have been conducted well. The evaluation of the context aspects revealed that the existence of the program is in line with the vision and mission of its founders. The program is also in line with the needs of the stakeholders. The evaluation of the input component indicated that adequate resources support the implementation of the program. This includes support from the leaders, existence of evaluation of the Tahfidz Qur'an program, availability of Tahfidz Qur'an teachers who fulfill standards, sufficient financial support, supporting facilities and infrastructure, various procedures and strategies used in the learning and teaching processes. The evaluation of the process revealed the implementation of the program is going well. This is proved by the suitability between the plan and implementation, the methods used, the allocation of time used starting from tahsin, guidance, memorization, as well as teacher assessment. The product evaluation revealed that of the 49 students at Grade Five, 33 students (67.3) achieved the required target, only two students (4.1%) did not meet the target, and 14 students (28.6%) exceeded the required target.